Designing Nonfullerene Acceptors with Oligo(Ethylene Glycol) Side Chains: Unraveling the Origin of Increased Open‐Circuit Voltage and Balanced Charge Carrier Mobilities. Issue 17 (21st July 2021) - Cui, Junjie; Park, Jung‐Hwa; Kim, Dong Won; Choi, Min‐Woo; Chung, Hae Yeon; Kwon, Oh Kyu; Kwon, Ji Eon; Park, Soo Young
Abstract: Despite the recent rapid development of organic solar cells (OSCs), the low dielectric constant ( ϵr =3–4) of organic semiconducting materials limits their performance lower than inorganic and perovskite solar cells. In this work, we introduce oligo(ethylene glycol) (OEG) side chains into the dicyanodistyrylbenzene‐based non‐fullerene acceptors (NIDCS) to increase its ϵr up to 5.4. In particular, a NIDCS acceptor bearing two triethylene glycol chains (NIDCS‐EO3) shows V OC as high as 1.12 V in an OSC device with a polymer donor PTB7, which is attributed to reduced exciton binding energy of the blend film. Also, the larger size grain formation with well‐ordered stacking structure of the NIDCS‐EO3 blend film leads to the increased charge mobility and thus to the improved charge mobility balance, resulting in higher JSC, FF, and PCE in the OSC device compared to those of a device using the hexyl chain‐based NIDCS acceptor (NIDCS‐HO). Finally, we fabricate NIDCS‐EO3 devices with various commercial donors including P3HT, DTS‐F, and PCE11 to show higher photovoltaic performance than the NIDCS‐HO devices, suggesting versatility of NIDCS‐EO3. Abstract : Introducing oligo(ethylene glycol) (OEG) chain into a dicyanodistyrylbenzene‐based nonfullerene acceptor (NIDCS) increased its dielectric constant ( ϵr ) from 3.3 to 5.4. The new NIDCS acceptor (NIDCS‐EO3) bearing two triethylene glycol chains showed improved open‐circuit voltages ( Voc ) and power conversion efficiencies (PCEs) with various donors in bulk heterojunction organic solar cells.